Telehealth and Medicare Type 2 Diabetes Care Outcomes: Evidence From Louisiana. Issue 4 (9th April 2023) - Walker, Brigham; Stoecker, Charles; Shao, Yixue; Nauman, Elizabeth; Fort, Daniel; Shi, Lizheng
Abstract : Background: At the onset of the COVID-19 pandemic, the Centers for Medicare and Medicaid Services broadened access to telehealth. This provided an opportunity to test whether diabetes, a risk factor for COVID-19 severity, can be managed with telehealth services. Objective: The objective of this study was to examine the impacts of telehealth on diabetes control. Research Design: A doubly robust estimator combined a propensity score–weighting strategy with regression controls for baseline characteristics using electronic medical records data to compare outcomes in patients with and without telehealth care. Matching on preperiod trajectories in outpatient visits and weighting by odds were used to ensure comparability between comparators. Subjects: Medicare patients with type 2 diabetes in Louisiana between March 2018 and February 2021 (9530 patients with a COVID-19 era telehealth visit and 20, 666 patients without one). Measures: Primary outcomes were glycemic levels and control [ie, hemoglobin A1c (HbA1c) under 7%]. Secondary outcomes included alternative HbA1c measures, emergency department visits, and inpatient admissions. Results: Telehealth was associated with lower pandemic era mean A1c values [estimate=−0.080%, 95% confidence interval (CI): −0.111% to −0.048%], which translated to an increased likelihood of having HbA1c in control (estimate=0.013; 95% CI: 0.002–0.024; P <0.023). Hispanic telehealth users had relatively higher COVID-19 era HbA1c levels (estimate=0.125; 95% CI: 0.044–0.205; P <0.003). Telehealth was not associated with differences in the likelihood of having an emergency department visits (estimate=−0.003; 95% CI: −0.011 to 0.004; P <0.351) but was associated with more the likelihood of having an inpatient admission (estimate=0.024; 95% CI: 0.018–0.031; P <0.001). Conclusion: Telehealth use among Medicare patients with type 2 diabetes in Louisiana stemming from the COVID-19 pandemic was associated with relatively improved glycemic control.